Application of the Finite Element Method in Modeling Biological Systems in Traumatology and Orthopedics - J. T. Tukhtaev; K. Kh. Mamadjonov; O. N. Abdulazizov; N. T. Botirov (Zien Journals, 2023)
Surgical treatment of fractures of the proximal femur is a problem due to the lack of a uniform treatment strategy. Of particular importance is the analysis of the processes occurring in bone tissue during the healing of fractures under dynamic conditions, especially the analysis of mechanical stresses. The finite element method is an effective method for mathematical modeling of complex objects and describing the stress-strain states of these objects. In order to improve the results of treatment of fractures of the proximal femur and pelvic bones, mathematical modeling was carried out using the finite element method of a pertrochanteric femur fracture under conditions of fixation with a dynamic pin and a pelvic fracture under various conditions of its submersible fixation
Keywords: finite element method; femur; pelvic bones